2017
DOI: 10.1021/acscatal.7b01095
|View full text |Cite
|
Sign up to set email alerts
|

Support Induced Control of Surface Composition in Cu–Ni/TiO2 Catalysts Enables High Yield Co-Conversion of HMF and Furfural to Methylated Furans

Abstract: 5-(Hydroxymethyl)furfural (HMF) and furfural (FF) have been identified as valuable biomass-derived fuel precursors suitable for catalytic hydrodeoxygenation (HDO) to produce high octane fuel additives such dimethyl furan (DMF) and methyl furan (MF), respectively. In order to realize economically viable production of DMF and MF from biomass, catalytic processes with high yields, low catalyst costs, and process simplicity are needed. Here, we demonstrate simultaneous coprocessing of HMF and FF over Cu−Ni/ TiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 99 publications
7
170
0
Order By: Relevance
“…Regeneration of the used catalysts was performed via calcination at 450°C for 5 h followed by reduction with pure H 2 at 450°C for 3 h. with TEMbased energy dispersive spectroscopy revealed that all observed metal particles contained both Cu and Ni, suggesting consistent formation of bimetallic particles. 39 The analysis was consistent with characterization using temperature-programmed reduction and X-ray diffraction, which both showed evidence of the formation of bimetallic particles. On the basis of this previous analysis, we focused here on analyzing the influence of Ni loading on the structure (both geometric and spatially varying composition) of the Cu−Ni bimetallic particles.…”
Section: ■ Materials and Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…Regeneration of the used catalysts was performed via calcination at 450°C for 5 h followed by reduction with pure H 2 at 450°C for 3 h. with TEMbased energy dispersive spectroscopy revealed that all observed metal particles contained both Cu and Ni, suggesting consistent formation of bimetallic particles. 39 The analysis was consistent with characterization using temperature-programmed reduction and X-ray diffraction, which both showed evidence of the formation of bimetallic particles. On the basis of this previous analysis, we focused here on analyzing the influence of Ni loading on the structure (both geometric and spatially varying composition) of the Cu−Ni bimetallic particles.…”
Section: ■ Materials and Methodssupporting
confidence: 78%
“…Given our previous conclusion that observed support effects on FF HDO reaction selectivity were not significantly influenced by differences in metal particle size of the same magnitude of variation observed here, we focused on analyzing the spatial distribution of Cu and Ni in bimetallic particles as a function of metal and support composition. 39 We note that differences in metal particle sizes as a function of support influenced the inherent reactivity of the catalysts.…”
Section: ■ Materials and Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…When compared to activity results reported in literature, the results reported herein are quite promising. First of all, binary Cu−Al 2 O 3 catalyst systems for FUR conversion to 2MF have mostly been tested in a batch reactor, indicating that our activity results obtained with a continuous reaction system will be useful in future reports. On the other hand, Jiménez‐Gómez et al reported selective production of 2MF over supported Cu on mesoporous silica (denoted as 10Cu‐MS).…”
Section: Structural Characteristics Of Catalysts Synthesized Under DImentioning
confidence: 99%